Design Of Monitoring Information System Stock Items At Partner Stores In Web-Based Semarang - Michael Danny Irawan; Albertus Dwiyoga Widiantoro; Agus Cahyo Nugroho (Journal of Business and Technology, 2022)
Toko Mitra is a grocery or retail store that is engaged to meet daily needs. Monitoring stock and transaction financial reports at Partner Stores in Semarang often experience problems. This is because the shop owner still uses a manual system, so that the recording of incoming and outgoing goods still does not match the last stock. Therefore, I want to provide a solution to Partner Shop owners by creating a web-based stock monitoring program. In building a stock monitoring system, I use programming languages PHP and JavaScript, MySQL as a database, and the CodeIgniter framework. The existence of a web-based stock monitoring system at Partner Stores is expected to help monitor activities that occur in the store to make it faster and more efficient.